Quantification of Retinal Vessel Myogenic Constriction in Response to Blood Pressure Peaks: Implications for Flicker Light-Induced Dilatation - Streese, Lukas; Vaes, Anja; Infanger, Denis; Roth, Ralf; Hanssen, Henner (Frontiers in Physiology, 2021)
Background/Aims: Flicker-light induced retinal vessel dilatation (FID), a marker of microvascular endothelial function, has been shown to be blunted in sedentary cardiovascular risk patients (SR) as well as healthy physically active individuals (HA). This study aimed to quantify the retinal myogenic response to blood pressure (BP) peaks and its effects on consecutive FID for differentiation of microvascular health. Methods: Ten HA and eleven SR with a previously established restriction of arteriolar FID (aFID) (<2.2%) were invited in order to assess BP-induced myogenic constriction following a standardized handgrip task and a consecutive FID. BP was measured beat-to-beat. Results: The complete dataset of nine HA (3 female, mean age 65 years) and nine SR (5 female, mean age 61 years) individuals was analysed. The central retinal arteriolar diameter equivalent (CRAE) was 183±11µm for HA and 176±20µm for SR. Initial baseline aFID was 1.6±0.4% in HA and 1.6±0.7% in SR. Systolic (p=0.334) and diastolic (p=0.245) BP increase following the handgrip task was in the range of 20-30% and comparable in both groups. BP increase was followed by a significantly higher arteriolar (-2.9±1.3% vs. -1.3±0.6%, p<0.01) myogenic constriction in HA compared to SR. Moreover, in the consecutive assessment of FID directly after the BP-induced vessel constriction, aFID (4.1±2.0% vs. 1.6±0.9%, p<0.01) was higher in HA compared to SR. Conclusion: Initial baseline aFID was blunted in HA and SR. Retinal myogenic constriction was impaired in SR compared to HA. The consecutive aFID after BP-induced myogenic constriction recovered in HA but remained blunted in SR. Additional assessment of retinal myogenic constriction needs to be considered to improve CV risk stratification and reduce false-positive findings of endothelial dysfunction in otherwise healthy active individuals.